MELATONIN AS AN ADDITIVE TO SHIELD THE HAZARDOUS EFFECTS OF CRYOPRESERVATION ON KANKREJ BULL SEMEN - KAPADIYA, P S; NAKHASHI, H C; SUTARIA, T V; RATHOD, B S; SUTHAR, B N (The Indian Journal of Animal Reproduction, 2022)
Melatonin was supplemented at 1, 2 and 3 mM in Tris-Fructose Egg Yolk Citrate Glycerol (TFYG) extender to assess the impact on various seminal and acrosomal characteristics of 24 ejaculates collected from Kankrej bulls (n=3). In brief, melatonin supplementation at 2 mM increased (p
Keywords: Cryopreservation; Kankrej bull,; Melatonin; Semen; Seminal characteristics